The attractiveness of the teaching profession: a integrative literature review - Thomas Dotta, Leanete; Rodrigues, Sónia; Joana, Luciana; Carvalho, Maria João (Frontiers in Education, 2025)
The widespread shortage of teachers highlights the urgent need to examine the factors influencing the attractiveness of the teaching profession. This issue is driven by high rates of early-career attrition, an ageing workforce, and a decline in candidates entering teacher education programs. Understanding the factors that make the profession appealing—or unappealing—has become essential for ensuring educational quality and equity. An integrative literature review was conducted to identify the key themes related to the attractiveness of the teaching profession, synthesizing evidence from multiple studies and highlighting research gaps. Findings reveal that teaching still attracts candidates driven by intrinsic motivations and social utility. However, external factors such as low salaries, challenging working conditions, and limited career progression remain significant deterrents. The social image of teaching, shaped by media and community perceptions, also influences career choices. The intersection of demographic shifts and educational policy changes highlights the complexity of addressing teacher shortages. Despite increased attention from policymakers, significant gaps remain, particularly in relation to interventions that reduce early-career attrition and support teacher retention. Future research should explore targeted strategies to support early-career teachers and examine the socio-economic factors that influence career decisions. Addressing these issues is critical to developing sustainable policies that enhance the attractiveness of the teaching profession and promote educational equity.